Inverse Emulsion Polymerization of Dimethyl Diallyl Ammonium Chloride and Acrylamide for Water Treatment - Zhang, Peng; Ren, Bozhi (Asian Journal of Chemistry, 2013)
Polymerization of dimethyl diallyl ammonium chloride and acrylamide (PDA) has been formed by using industrial dimethyl diallyl ammonium chloride (DMDAAC) and industrial acrylamide (AM) initiated by K2S2O8-NaHSO3. The effect of reaction variables such as concentration of the reactants, reactants ratio, dosage of EDTA and reaction time were investigated and the product was detected and characterized with IR spectroscopy and thermo gravimetric analysis. The DBP removal efficiency by PDA was investigated. In the batch mode of studies, the pH value and effect of the intrinsic viscosity of product were investigated and when the initial concentration of simulated water was 0.5 mg/L, pH value of 10, dosage of PDA was 8 mg/L, the removal efficiency of DBP reached a maximum value 92.4 %.